Babesiosis with low parasitemia as a cause of secondary hemophagocytic lymphohistiocytosis in a previously healthy adult - Max W. Jacobs; Joseph M. Rocco; Lisa K. Andersen; Thomas E. Robertson (IDCases)
The incidence of babesiosis is increasing and clinicians should have a high index of suspicion due to its diagnostic challenges and variable disease course, from asymptomatic infection to fulminant disease. We present a case of fatal secondary hemophagocytic lymphohistiocytosis (sHLH) due to acute babesiosis in a previously healthy adult. We also present a comprehensive review of previously reported sHLH cases triggered by babesiosis. Host factors, such as immunocompromising conditions or medications, appear to be a risk factor for developing sHLH while it is unclear if percent parasitemia of babesia correlates with development or outcomes of HLH. Increasing awareness to improve time to diagnosis is vital for treating both babesiosis and sHLH, while future studies should investigate the role for immunomodulator therapy in this setting.